Risk management in the management control system in polish local government units: Assumptions and practice - Katarzyna Mormul (Risks, 2021)
The issues related to management control and risk management are related not only to the safe operation of a given organization, but also contribute to ensuring the continuity of its operations. The main purpose of this article is to present the general principles of the organization of the management control and risk management system and to check the knowledge of its essence and principles by the employees of local government units. In the empirical part of the article, the method of desk research was used, as well as a questionnaire, which check the knowledge of rules and procedures by local government units' employees. The research results show that the understanding of the essence and principles of management control system and risk management by employees is incomplete. Therefore, it is recommended to conduct training in the field, increasing the knowledge of the management control system. This is important because a properly functioning management control system may contribute to the improvement of public service provision, better use of resources, and may also prevent wastage.
Keywords: 330; management control; risk; risk management; local government units